2016
DOI: 10.1188/16.cjon.e3-e8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Oncology: Evolution of Postoperative Fatigue and Factors Related to Its Severity

Abstract: The prevalence of moderate and severe fatigue varies during the postoperative period, with a reduction in the 12 months after surgery. Various factors (e.g., stress, anxiety, depression, pain, changes in sleep patterns) seem to influence the severity of fatigue. More evidence is needed to explore the relationship between immediate postoperative fatigue and the evolution of fatigue during the period following surgical treatment for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
1
14
0
5
Order By: Relevance
“…[ 18 ] In fact, most of the evidence related to the postoperative period was obtained during the first 7 days after surgery, if there is no early intervention, it will last longer, even 12 months after surgery. [ 19 ] It may also cause secondary complications, prolong the length of hospital stay, and affect the patients’ return to society. [ 20 ] Acupoint massage stimulates acupoints by massage, so as to adjusting activity of Qi, activate meridians, promote blood circulation, strengthen metabolism, enhance immunity and promote sleep, so as to achieve the balance of Yin and Yang and relieve fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] In fact, most of the evidence related to the postoperative period was obtained during the first 7 days after surgery, if there is no early intervention, it will last longer, even 12 months after surgery. [ 19 ] It may also cause secondary complications, prolong the length of hospital stay, and affect the patients’ return to society. [ 20 ] Acupoint massage stimulates acupoints by massage, so as to adjusting activity of Qi, activate meridians, promote blood circulation, strengthen metabolism, enhance immunity and promote sleep, so as to achieve the balance of Yin and Yang and relieve fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Average postoperative nausea intensity in the present study reflected sleeping difficulties; sleeping quality in turn has been found to have an impact on postoperative physical recovery (Gong, Wang, & Fan, ; Miller, Roth, Roehrs, & Yaremchuk, ). Furthermore, sleep restriction is believed to increase perceived pain intensity (Tiede et al., ) and experience of fatigue (Oliveira, Oliveira, Souza‐Talarico, & Mota, ). The recovery aspect of fatigue was associated with nausea intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Class 2, characterized by a downswing in the first period and followed by a plateau, typically comprised patients who recovered from postoperative fatigue. Oliveira et al (28) reported that fatigue after surgery in tumor patients decreased significantly in the first 2 months and persisted weekly thereafter. The trajectory of class 3 involved the highest initial level rise and then a plateau, suggesting that hormone symptoms in these patients are more obvious.…”
Section: Hormone Related Symptomsmentioning
confidence: 99%